Mercy Watson : princess in disguise. - DiCamillo, Kate (Cambridge, Mass. : Candlewick Press, 2007)
Persuaded by the word "treating" to dress up as a princess for Halloween, Mercy the pigś trick-or-treat outing has some very unexpected results.
Keywords: Pigs--Fiction; Halloween--Fiction